Pengaruh risiko kredit, inflasi, dan BI Rate terhadap profitabilitas LPN Limau Manih - Yonita, Riza; Linda, Muthia Roza (Jurnal Kajian Manajemen Bisnis, 2019)
This study aimed to analyze the effect of (1) credit risk on the profitability of the Limau Manih LPN, (2) inflation on the profitability of the Limau Manih LPN and (3) the BI Rate on the profitability of the Limau Manih LPN. The object of research is the Limau Manih LPN. The type of data used in this study is secondary data obtained from the company's annual report with observations ranging from 2009-2017. The analytical method used is multiple regression analysis. The results of this study conclude (1) credit risk which is proxied by NPL has a positive and significant effect on profitability in the Limau Manih LPN, (2) inflation has a positive and not significant effect on profitability in the Limau Manih LPN, and (3) the BI Rate has a positive and no effect significant effect on profitability at the Limau Manih LPN.Keywords: Profitability; credit risk, inflation; BI Rate.